Life cycle sustainability assessment of repair through wire and arc additive manufacturing - Pagone, Emanuele; Antonissen, Joachim; Martina, Filomeno (Springer, 2022)
Extending the useful life of a product through repair can significantly reduce the environmental impact associated with its production, and it can be less resource intensive than other environmentally virtuous practices like recycling. Wire and arc additive manufacturing (WAAM) appears to be a promising approach in this context, being characterized by high-resource efficiency, flexibility to perform repairs, and having recently gained industrial maturity. In this work, a methodology to assess the life cycle environmental sustainability of repaired products through WAAM will be presented with a real-world, industrial case study.
Keywords: Sustainability; Additive manufacturing; Modeling and simulation